Interpretaciones sobre la deforestación en áreas naturales protegidas en la Amazonía del Perú - Dourojeanni, Marc (2023)
This note comments and criticizes some aspects of a recent publication (Cotrina A. et al. 2021. «Peruvian Amazon disappearing: Transformation of protected areas during the last two decades (2001-2019) and potential future deforestation modeling using cloud computing and MaxEnt approach». Journal for Nature Conservation, Elsevier) that analyzes year by year deforestation in Peruvian Amazon protected natural areas and in their buffer zones. Their results are interesting and they generally confirm what is known on the subject. However, in addition to making inaccurate statements, the authors of this work draw alarmist conclusionsthat are not consistent with their own results or with the reality of managing protected natural areas in Peru and other tropical countries.